Bersih 5 and the Growing Discontent among the Malays - Malik, Maszlee; Hew, Wai weng (Ishak Institute, Singapore, 2016)
More than 50,000 people took part in the Bersih 5 demonstration in Kuala Lumpur on 19 November 2016 calling for fair and clean elections. This was despite threats of violence by an opposing group, the arrest of some of the Bersih movement’s key leaders and the blocking of road access by the police.